A new genus and species of feather duster worm (Annelida, Sabellidae) from shallow hydrocarbon seeps in the Gulf of Mexico - Lauren Rice; María Ana Tovar-Hernández; Christina Ellison; Craig Young (Biodiversity Data Journal, 2025)
Sabellid species are known to have a broad depth distribution and have been reported from various deep-sea habitats, including chemosynthetic systems. Despite this presence, only two species have been identified from deep water chemosynthetic habitats and only one has been identified to species. When examining hydrocarbon seep systems along the Upper Louisiana Slope in the Gulf of Mexico, we observed an abundant sabellid species new to science. The characters for the collected specimens did not match any existing genus.The description for the new sabellid genus and species are presented, supported by external morphology and DNA sequence data (cytochrome c oxidase I). Seepicola viridiplumi gen. nov., sp. nov. are gregarious, facultative hyper-epibionts within the examined methane seep communities and, seemingly, have a blend of morphological features of the genera Perkinsiana and Pseudopotamilla. Specimens also have several distinctive characters including the presence of a pair of peristomial chambers between the ventral lappets and parallel lamellae and the short, button-like shape of the radiolar tips. Abundance estimates for S. viridiplumi gen. nov., sp. nov. within the seep habitats are also presented.